Adaptive Reliability Engineering for Transaction-Intensive Enterprise Platforms - Chandramouli Holigi (International Journal of Computational and Experimental Science and Engineering, 2026)
Reliability engineering for transaction-intensive distributed platforms has evolved beyond static provisioning and threshold-based fault tolerance. Modern cloud-native systems operate under nonlinear workload volatility, metastable degradation risks, and complex dependency-induced failure propagation, rendering traditional reliability models insufficient.This paper formalizes Adaptive Reliability Engineering (ARE) as a control-theoretic framework that transforms reliability from static configuration into a closed-loop operational discipline. By integrating real-time telemetry, dynamic load shedding, health-aware routing, circuit breaker isolation, and feedback-driven resource governance, ARE enables continuous system stabilization under volatile demand conditions.The framework addresses metastable failure amplification, retry-induced cascading collapse, and inefficiencies in error-path execution by introducing adaptive control surfaces that dynamically regulate resource allocation and service-level objective (SLO) compliance.Unlike machine learning–dependent resource managers that require prolonged training cycles and exploration overhead, ARE emphasizes deterministic feedback control mechanisms capable of immediate responsiveness without extended data collection phases.The proposed framework generalizes across financial transaction infrastructures, digital commerce platforms, and cloud-native microservices architectures.